The catena to James: reading the Letter of James in the Ancient Greek commentary tradition - Albl, Martin C. (Texts and editions for New Testament study, 2024)
Intro -- ‎Contents -- ‎Acknowledgments -- ‎Abbreviations -- ‎Introduction -- ‎1. The Contribution of This Study -- ‎1.2. Locating CatJas within Broader Catena Studies -- ‎2. The Catena Genre and Associated Terminology -- ‎2.1. Defining the Catena Genre -- ‎2.2. The Value of Studying Catena Traditions -- ‎2.3. Forms of the Catenae -- ‎2.4. Ancient Terminology for the Catenae -- ‎2.5. Further Terminology for Catena Study -- ‎3. Historical Background of the Catena Genre in Ancient Jewish Literature? -- ‎4. Historical Background of the Catena Genre in Hellenistic Education and Scholarship -- ‎4.1. The Catena and the Hellenistic Educational System -- ‎4.2. The Catena and Greco-Roman and Early Christian Use of Anthologies -- ‎4.3. Commentaries, Marginal Comments, and the Catena Genre -- ‎5. A Brief History of the Catenae -- ‎5.1. Procopius of Gaza and the Origins of the Exegetical Catenae -- ‎5.2. Catenae before Procopius? -- ‎5.3. Dates of Other Catenae Traditions -- ‎5.4. Palestinian and Constantinopolitan Catena Traditions -- ‎5.5. Compilers of the Catenae -- ‎5.6. Historical Changes in the Form of the Catenae -- ‎5.7. Analyzing Catena Traditions -- ‎5.8. Libraries and Catena Traditions -- ‎6. The Inclusive Nature of the Catenae -- ‎7. CatCE and Euthalian Traditions -- ‎7.1. Euthalian Chapter Divisions and Titles in CatJas -- ‎7.2. Other Introductory Material in the Euthalian Tradition -- ‎7.3. Relationship of the Euthalian Materials and CatJas -- ‎8. Manuscripts and Printed Editions of CatCE -- ‎8.1. Main Manuscripts of CatCE -- ‎8.2. Printed Editions -- ‎8.3. Translations of CatCE -- ‎9. Unattributed Sources of CatCE -- ‎9.1. The Anonymous Commentary (AC) on the Catholic Epistles -- ‎9.2. Staab's Analysis of the AC -- ‎9.3. The Textual Witnesses of the AC -- ‎9.4. Profile of the AC -- ‎9.5. The Relationship between the AC and CatJas.